The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1097/ta.0000000000001116
|View full text |Cite
|
Sign up to set email alerts
|

CD43Lo classical monocytes participate in the cellular immune response to isolated primary blast lung injury

Abstract: BackgroundExplosive blast trauma occurs by four mechanisms: primary injuries are due to the isolated effect of the blast wave on the human body, secondary injuries are due to damage from fragments energised from the explosion, tertiary injuries result from acceleration of the body against an object or through the explosion energising hard materials in a solid form (not fragments) and encroaching upon the person, and quaternary injuries describe other physical insults, including burns and smoke inhalation 1 .Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In real terms, this equates to a small region ~0.1 mm 3 (Zone 1) that may be obviously damaged by the blast, potentially compromising a region 10 times that size in terms of the mechanics. The fact this is not observed throughout the specimen nor affecting the greater surrounding region of this lung volume (100% or full volume) supports the fact that this is a moderate-blast condition and a non-lethal dose (Barnett-Vanes et al, 2016).…”
Section: Exx Exy Exz Eyx Eyy Eyz Ezx Ezy Ezzmentioning
confidence: 60%
See 4 more Smart Citations
“…In real terms, this equates to a small region ~0.1 mm 3 (Zone 1) that may be obviously damaged by the blast, potentially compromising a region 10 times that size in terms of the mechanics. The fact this is not observed throughout the specimen nor affecting the greater surrounding region of this lung volume (100% or full volume) supports the fact that this is a moderate-blast condition and a non-lethal dose (Barnett-Vanes et al, 2016).…”
Section: Exx Exy Exz Eyx Eyy Eyz Ezx Ezy Ezzmentioning
confidence: 60%
“…Applied blast pressures (Figure 3) were in or below the level of the reported thresholds for lung injury (CR Bass et al, 2008). Previous research on BLI suggested the moderate blast case is survivable with no observable structural damage (Barnett-Vanes et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations